Penguatan Literasi Kesehatan Puasa Ramadhan pada Peserta Program Pengelolaan Penyakit Kronis (PROLANIS) - Pandith Aribowo Arismunandar; Lucky Wardani; Sri Maryati (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2026)
Non-communicable diseases such as Diabetes Mellitus (DM) and hypertension are leading causes of global morbidity and mortality and require comprehensive long-term management. During Ramadan, alterations in dietary patterns, medication schedules, and physical activity may increase the risk of complications among patients with chronic conditions. A situational analysis of participants enrolled in the Chronic Disease Management Program (PROLANIS) at Klinik Pratama Sehat Budi Luhur Cimahi revealed limited understanding regarding safe fasting criteria and recognition of danger signs. This community service initiative aimed to enhance participants’ knowledge of safe fasting guidelines. The intervention employed an interactive educational session combined with discussion and evaluation through pre-test and post-test assessments involving 21 PROLANIS participants diagnosed with DM and hypertension. Pre-test results indicated that only 33.3% of participants demonstrated good knowledge, while 19.1% were categorized as having poor knowledge. Following the intervention, post-test results showed a significant improvement, with 100% of participants achieving a good knowledge level. These findings suggest that structured education effectively improves participants’ understanding of risk stratification, therapy adjustment, dietary management, and self-monitoring practices during fasting. In conclusion, community-based education delivered through the PROLANIS framework represents an effective promotive and preventive strategy to support DM and hypertension management during Ramadan. Regular implementation of similar educational programs is recommended to sustain adherence and prevent long-term complications.